A Revision of the "Auxiliaries" Class of Sakhalin Ainu: Data from the Pilsudski Corpora - Dal Corso Elia (Manggha Museum, 2020)
This paper investigates a number of formal devices found in Sahkalin Ainu with regards to both their morphosyntactic properties and their semantico-pragmatic features. I develop my account on these formal devices from the analysis in Murasaki (1979), who discusses them as jodōshi rengo “auxiliary verb constructions” on the basis of how they seem to contribute to the meaning of a notional verb they accompany, the scope of her observations being her edited corpus of Western Sakhalin Ainu (WSA) folktales and conversations (Murasaki, 1976). Here I broaden my approach to “auxiliary verb constructions” by taking into account also their occurrences in the Eastern Sakhalin dialect of Ainu (ESA) as documented in the language materials collected by Piłsudski, and by adding a few elements featured in this latter dialect that are unaccounted for in WSA. Until more appropriate labels are proposed, I will generically refer to all the elements of WSA and ESA under scrutiny as “auxiliaries”. My observations concern the morphosyntactic and semantico-pragmatic behaviors of “auxiliaries”, which I then compare to the properties of auxiliaries as outlined in typological works, to see to what extent (if at all) they comply with the typological prototype. Eventually, I depart from Murasaki’s classification by arguing that only a few elements in her original list are in line with the prototypical behaviors of auxiliaries, and I propose that all other elements are better discussed as belonging to separate classes, among which light verbs, adverbs, and final particles. Moreover, I show how in some cases the data from the Piłsudski corpora are crucial for refining my final classification. This study represents an attempt to improve the classification of “auxiliaries” of Sakhalin Ainu, by looking at them from a cross-dialectal and typological perspective. Furthermore, it considers language data coming from the Piłsudski corpora, a resource that is rarely used for descriptive works on Sakhalin Ainu to date.